2004
DOI: 10.1016/j.cub.2004.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Rictor, a Novel Binding Partner of mTOR, Defines a Rapamycin-Insensitive and Raptor-Independent Pathway that Regulates the Cytoskeleton

Abstract: The mammalian TOR (mTOR) pathway integrates nutrient- and growth factor-derived signals to regulate growth, the process whereby cells accumulate mass and increase in size. mTOR is a large protein kinase and the target of rapamycin, an immunosuppressant that also blocks vessel restenosis and has potential anticancer applications. mTOR interacts with the raptor and GbetaL proteins to form a complex that is the target of rapamycin. Here, we demonstrate that mTOR is also part of a distinct complex defined by the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

84
2,332
3
46

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,432 publications
(2,465 citation statements)
references
References 21 publications
84
2,332
3
46
Order By: Relevance
“…This also was observed for rictor, a component of mTOR complex 2 (mTORC2) which provides substrate specificity for AKT 14. Protein kinase Cα (PKCα), which is phosphorylated by mTORC2 at serine 657,15, 16 was present and phosphorylated identically in resting platelets from all horses and throughout the time course after activation with α‐thrombin (Fig 4B).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This also was observed for rictor, a component of mTOR complex 2 (mTORC2) which provides substrate specificity for AKT 14. Protein kinase Cα (PKCα), which is phosphorylated by mTORC2 at serine 657,15, 16 was present and phosphorylated identically in resting platelets from all horses and throughout the time course after activation with α‐thrombin (Fig 4B).…”
Section: Resultssupporting
confidence: 55%
“…Normal levels of the mTORC2 components rictor and mTOR, as well as normal phosphorylation of the mTORC2 target serine 657 of PKCα after activation, provide evidence that this complex functions normally in AET platelets 15, 16. Although recent studies have shown that pharmacological inhibition of mTORC2 does not inhibit aggregation of washed platelets, the role of this complex in fibrinogen binding and α‐granule secretion remains undefined 14, 24.…”
Section: Discussionmentioning
confidence: 99%
“…These complexes differ in their major binding partner: raptor (regulatory-associated protein of TOR) in mTORC1 and rictor (rapamycin-insensitive companion of mTOR) in mTORC2 (REFS 23 ,24 ) (FIG. 2).…”
Section: Mtor Kinase Complexes and Their Activitiesmentioning
confidence: 99%
“…mTOR is an evolutionarily conserved serine/threonine protein kinase which is constituted by two signaling complexes: mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2). Both complexes have specific effects on distinct cellular functions, such as controlling mRNA translation, ribosome biogenesis, autophagy and metabolism (4)(5)(6). mTORC2 phosphorylates AGC kinases such as AKT, serum-and glucocorticoid-induced protein kinase-1 (SGK1) and protein kinase C-alpha (PKCα) (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%